Pengaruh Kreativitas Belajar, Kemandirian Belajar, dan Kecerdasan Emosional Terhadap Hasil Belajar Mata Pelajaran Akuntansi Dasar pada Siswa Kelas X SMK Negeri di Jakarta Barat - Cicih Nonia; Adam Zakaria; Sri Zulaihati3 (Universitas Serambi Mekkah, 2025)
Independence, and Emotional Intelligence on Learning Outcomes of Basic Accounting Subjects on Grade X Students of State Vocational High School in West Jakarta. This study used a survey method with a quantitative approach. With an affordable population of 180 students from two schools, namely SMK Negeri 13 Jakarta Barat and SMK Negeri 17 Jakarta Barat. The sample in this study was 119 respondents with proportional random sampling technique and the Isaac and Michael formula. The data collection method in this study used a questionnaire method. This study uses data analysis techniques, namely multiple regression equations, data analysis requirements tests (test for normality and linearity), hypothesis tests (T test and F test) and coefficients of determination. Normality test with Kolmogorov Smirnov on both variables has a value of 0.200. With the results of the linearity test on Learning Creativity, Learning Independence and Emotional Intelligence worth >0.001. The F test is worth 628.116 and the T test on the variable of learning creativity is worth 23.468, learning independence variable is worth 30.986 and the emotional intelligence variable is worth 23.787. The result of the multiple regression equation is Y = 0,081 + 0,288(X1) + 0,395(X2) + 0,299 (X3). The results of this study indicate a significant influence between learning creativity, learning independence, and emotional intelligence on learning outcomes, this is proven by the coefficient of determination value of 0.942, which means that 94.2% of the learning outcomes variables are related simultaneous can be explained by the learning creativity, learning independence and emotional intelligence while the remaining 5.8% is influenced by other factors not examined by researchers.